Monitoring Bimbingan Skripsi Online Pada Sekolah Tinggi Manajemen Informatika Dan Komputer (STMIK) Palangka Raya - Utariani, Utariani; Herkules, Herkules (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
The problem of this research is how to design and build a web-based application to make the process of thesis guidance. This app aims to help the process of guidance and help students who are taking the thesis and lecturers also may correct student thesis, so that the process runs smoothly guidance to complete. Further, the application also helps faculty in monitoring students in conducting guidance The methods used in this research for observational data collection is interview, and literature, for software development methods we using the waterfall model, software testing methods using Black Box Testing and methods for analysis system weaknesses using PIECES. This research has been successfully implemented an Application Monitoring Guidance thesis on the School of Information Management and Computer Palangkaraya Based Web using codeigniter 3.0 and has been successfully tested against the results of the implementation.The application can provide convenience for students who are doing a thesis on STMIK Palangka raya.